Software Development Metrics With a Purpose - Gonzalez-Barahona, Jesus M.; Izquierdo-Cortazar, Daniel; Robles, Gregorio; Riehle, Dirk (Computer, 2022)
A new generation of toolsets that are flexible enough to adapt to the data analytics needs of a given scenario is emerging to analyze free, open source software (FOSS). GrimoireLab is one such toolset that meets many of the needs of foundations, developers, and companies.
CRIS-Team Scopus Importer:2024-12-16